Development of efficient VoIP application using cognitive radio networks - Sharanya, C; Meena, M; Monisha, M; V. Rajendran, Dr; ., . (International Journal of Engineering and Technology, 2018)
There is an increased usage of wireless communication for personal use, commercial use etc. Nowadays Cognitive Radio has become the prime topic of interest in wireless network. It is an intelligent radio technology, which easily adapts to the network and automatically detects the vacant channels which are available in a wireless spectrum. It then changes the transmission parameters enabling concurrent communica-tions thereby improving the radio operating behavior. VoIP mobile applications are used worldwide for making audio and video calls using internet. But they face many disadvantages such as reflection of voice/echo, breaking of voice, delay in voice etc and have reduced quality with low Wi-Fi or 3g signals. Therefore we are designing an efficient and effective system to improve throughput and bit error rate of VoIP mobile applications by implementing them using cognitive radio networks.Â